2007
DOI: 10.1097/01.olq.0000245915.38315.bd
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Human Papillomavirus Vaccination Acceptability Among Underserved Women

Abstract: The current study highlights key correlates of vaccine acceptability that may inform HPV vaccination campaigns for underserved populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
108
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(116 citation statements)
references
References 21 publications
5
108
3
Order By: Relevance
“…Existing studies have shown that knowledge about HPV may strongly influence vaccination acceptance (Gerend et al, 2007;Gottvall et al, 2009). In China, there have been some studies examining this topic, both in Hong Kong Kwan et al, 2008;Kwan et al, 2009) and in mainland China Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies have shown that knowledge about HPV may strongly influence vaccination acceptance (Gerend et al, 2007;Gottvall et al, 2009). In China, there have been some studies examining this topic, both in Hong Kong Kwan et al, 2008;Kwan et al, 2009) and in mainland China Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Although infections with "low-risk" HPV types (HPV 6,11) are generally benign, they can lead to low-grade cervical cell changes, genital warts, and respiratory papillomatosis. Persistent infection with "high-risk" oncogenic HPV types (HPV 16,18) can cause cervical, oropharyngeal, and anogenital cancers (2). Black and Hispanic women experience a disproportionate burden of cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The Food and Drug Administration approved a quadrivalent vaccine (covering HPV types 6,11,16,18) in June 2006 for use among girls and women 9-26 years of age and approved a second bivalent vaccine (covering HPV types 16 and 18) in October 2009. The vaccine is most efficacious if administered before sexual debut (4).…”
Section: Introductionmentioning
confidence: 99%
“…This indicated that HPV immunization may be of particular benefit to the rural poor and medically underserved populations worldwide where women are deprived of access to regular cervical screening [19]. Several studies on acceptability of HPV vaccine among the underserved rural women have been reported in the literature [11,[20][21][22]. Lack of reported data from underdeveloped and developing regions warrants further investigation, especially in the context of a high population incidence of cervical cancer in these regions and even higher incidence among the marginalized women in rural areas.…”
Section: Introductionmentioning
confidence: 99%